Enhanced bacterial cancer therapy delivering therapeutic RNA interference of c-Myc - Jason Williams (Cell and Bioscience, 2024)
BackgroundBacterial cancer therapy was first trialled in patients at the end of the nineteenth century. More recently, tumour-targeting bacteria have been harnessed to deliver plasmid-expressed therapeutic interfering RNA to a range of solid tumours. A major limitation to clinical translation of this is the short-term nature of RNA interference in vivo due to plasmid instability. To overcome this, we sought to develop tumour-targeting attenuated bacteria that stably express shRNA by virtue of integration of an expression cassette within the bacterial chromosome and demonstrate therapeutic efficacy in vitro and in vivo.ResultsThe attenuated tumour targeting Salmonella typhimurium SL7207 strain was modified to carry chromosomally integrated shRNA expression cassettes at the xylA locus. The colorectal cancer cell lines SW480, HCT116 and breast cancer cell line MCF7 were used to demonstrate the ability of these modified strains to perform intracellular infection and deliver effective RNA and protein knockdown of the target gene c-Myc. In vivo therapeutic efficacy was demonstrated using the Lgr5creERT2Apcflx/flx and BlgCreBrca2flx/flp53flx/flx orthotopic immunocompetent mouse models of colorectal and breast cancer, respectively. In vitro co-cultures of breast and colorectal cancer cell lines with modified SL7207 demonstrated a significant 50–95% (P < 0.01) reduction in RNA and protein expression with SL7207/c-Myc targeted strains. In vivo, following establishment of tumour tissue, a single intra-peritoneal administration of 1 × 106 CFU of SL7207/c-Myc was sufficient to permit tumour colonisation and significantly extend survival with no overt toxicity in control animals.ConclusionsIn summary we have demonstrated that tumour tropic bacteria can be modified to safely deliver therapeutic levels of gene knockdown. This technology has the potential to specifically target primary and secondary solid tumours with personalised therapeutic payloads, providing new multi-cancer detection and treatment options with minimal off-target effects. Further understanding of the tropism mechanisms and impact on host immunity and microbiome is required to progress to clinical translation.